Case report of middle aged male patient with extra digital glomus tumor visiting dermatology clinic of King Abdul-Aziz Medical City, National Guard Health Affairs, Jeddah, Saudi Arabia, 2018 - Alamri, Awadh; Alahmadi, Marwan; Satti, Mohamed B.; Alruwaili, Amaal F.; Alotaibi, Homaid; Al-Mugti, Hani Saad (International Journal of Research in Dermatology, 2019)
Glomus tumors are rare, benign and vascular neoplasm of the glomus body, account for less than 2% of all soft tissue tumors. The most common site is the subungual region of the fingers and toes. Extra digital sites including the forearm are uncommon and usually misdiagnosed as other conditions. Usually the glomus tumors present with the classical triad of severe pain, pinpoint tenderness and clod hypersensitivity. This is a case report study design with detailed history, examination of 54-years-old male patient with a painful nodular lesion in the left forearm, which is misdiagnosed as foreign body granuloma. Elliptical excision relieved the symptoms and histopathologic examination confirmed the diagnosis of glomus tumor.